Analisis Pengaruh Strategi Promosi, Loyalitas dan Kepuasan Hidup Penggemar terhadap Niat Pembelian Kembali Album NCT Dream - Hanifah, Nur; Yusrin, Nur Amalyna (Penerbit Goodwood, 2024)
Purpose: This study aims to examine the influence of promotional strategies, fan loyalty, and life satisfaction on the intention to repurchase the NCT Dream album. Research methodology: A quantitative approach was used to collect data through questionnaires and data analysis techniques using regression with the SPSS 26 software. Results: The research results show that promotional strategies, loyalty and fan life satisfaction have a positive influence on repurchase intentions. Limitations: This research only focuses on NCT Dream fans in Indonesia; it was also conducted for 10 months so that fans’ repurchase intentions may change over this long period. Contribution: This research can be used by sellers who have a target market for fans of the boy group NCT Dream.